2019
DOI: 10.3892/ol.2019.10112
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of the pentose phosphate pathway in malignant tumors (Review)

Abstract: Interest in cancer metabolism has increased in recent years. The pentose phosphate pathway (PPP) is a major glucose catabolism pathway that directs glucose flux to its oxidative branch and leads to the production of a reduced form of nicotinamide adenine dinucleotide phosphate and nucleic acid. The PPP serves a vital role in regulating cancer cell growth and involves many enzymes. The aim of the present review was to describe the recent discoveries associated with the deregulatory mechanisms of the PPP and gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 108 publications
(111 reference statements)
4
130
0
1
Order By: Relevance
“…Dramatic changes in energy fluxes occur during carcinogenesis as supported by the massively perturbed protein expression profile in breast cancer tissue compared to normal breast tissue ( Figure 3A). Most notably, enzymes of the glycolytic pathway increase substantially ( Figure 3A and Figure S2A) supporting their dominant contribution to supply of energy and chemical components for cell proliferation in cancer tissue [50]. We also see enrichment of the pentose phosphate pathway ( Figure 3A and Figure S2A).…”
Section: Oral Nahco 3 Therapy Does Not Affect Tumor Burden Tumor-frementioning
confidence: 63%
“…Dramatic changes in energy fluxes occur during carcinogenesis as supported by the massively perturbed protein expression profile in breast cancer tissue compared to normal breast tissue ( Figure 3A). Most notably, enzymes of the glycolytic pathway increase substantially ( Figure 3A and Figure S2A) supporting their dominant contribution to supply of energy and chemical components for cell proliferation in cancer tissue [50]. We also see enrichment of the pentose phosphate pathway ( Figure 3A and Figure S2A).…”
Section: Oral Nahco 3 Therapy Does Not Affect Tumor Burden Tumor-frementioning
confidence: 63%
“…Cancer cells use glucose metabolism in order to supply the higher required proliferation rate, and, in particular, PPP is a metabolic pathway used both to synthesize nucleic acids and to maintain the cellular redox state [21,22].…”
Section: Glucose Metabolism and The Pentose Phosphate Pathway In Tumomentioning
confidence: 99%
“…The non-oxidative branch includes various reversible reactions, consisting of the conversion of different glycolytic intermediates such as fructose-6-phosphate (F6P) and glyceraldehyde-3-phosphate (G3P), into pentose phosphate and vice versa [21,22]. The main enzymes involved in non-oxidative PPP are transketolase (TKT) and transaldolase (TALDO).…”
Section: Glucose Metabolism and The Pentose Phosphate Pathway In Tumomentioning
confidence: 99%
“…Within the primary tumor, it has been shown that PDA cells can engage different mechanisms to regulate the levels of intracellular ROS. These include increased glucose flux through the pentose phosphate pathway (PPP) [73,74] and increased glutamine metabolism [75,76]. Both of these mechanisms result in a net increase in the levels of the reducing equivalent NADPH, which maintains the levels of intracellular reduced glutathione [77].…”
Section: Surviving Oxidative Changes In the Circulation And Distant Pmentioning
confidence: 99%